The Problem with Longtermism - Hyde, B.V.E. (Adam Mickiewicz University, Faculty of Philosophy, 2023)
Moral circle expansion has been occurring faster than ever before in the last forty years, with moral agency fully extended to all humans regardless of their ethnicity, and regardless of their geographical location, as well as to animals, plants, ecosystems and even artificial intelligence. This process has made even more headway in recent years with the establishment of moral obligations towards future generations. Responsible for this development is the moral theory – and its associated movement – of longtermism, the bible of which is What We Owe the Future (London: Oneworld, 2022) by William MacAskill, whose book Doing Good Better (London: Guardian Faber, 2015) set the cornerstone of the effective altruist movement of which longtermism forms a part. With its novelty comes great excitement, but longtermism and the arguments on its behalf are not yet well thought out, suffering from various problems and entailing various uncomfortable positions on population axiology and the philosophy of history. This essay advances a number of novel criticisms of longtermism; its aim is to identify further avenues for research required by longtermists, and to establish a standard for the future development of the movement if it is to ever be widely considered as sound. Some of the issues raised here are about the arguments for the moral value of the future; the quantification of that value with the longtermist ethical calculus – or the conjunction of expected value theory with the ‘significance, persistence, contingency’ (SPC) framework; the moral value of making happy people; and our ability to affect the future and the fragility of history. Perhaps the most significant finding of this study is that longtermism currently constitutes a shorterm view on the longterm future, and that a properly longterm view reduces to absurdity.
Keywords: Effective altruism; longtermism; historiosophy; ethical calculus; existential risk; future; William MacAskill